Hirsutidin protects against hepatic injury by alcohol-induced oxidative stress in mice - Fahad A. Al-Abbasi (Journal of Taibah University for Science, 2024)
In this research, the influence of hirsutidin on mice with alcoholic liver disease was examined. A total of 30 mice were randomly allocated to five groups (n = 6): Normal control group, Ethanol (EtOH) control group, hirsutidin-10, hirsutidin-20, and hirsutidin-20 per se for 4-week. Furthermore, 1 h after the last dosage of the treatment, 5 mL/kg (i.p.) EtOH (56%) was injected to cause hepatic injury. After 5 h of EtOH administration, blood samples were taken, and then the liver was excised for biochemical analysis. Hirsutidin treatment restored the biochemical changes induced by EtOH: serum levels of liver function tests, lipid profile, blood urea nitrogen, antioxidants levels, malondialdehyde, and cytokines. Hirsutidin supplementation also significantly decreased the histopathological abnormalities in EtOH-induced mice. In the present study, hirsutidin was found to have therapeutic potential for the treatment of alcoholic liver disease. Hirsutidin prevented ethanol-induced biochemical and histopathological alterations in the liver, suggesting its hepatoprotective effect.